Proses perencanaan penguatan sikap spritual dengan memanfaatkan pembiasaan yang ada di SDN Tembong - Nurhasanah, Ana; Bahctiar, Azye Albar; Nurmala, Nurmala; Yuliana, Yuliana (Educational Consultant & Counseling Career (EC3) Mataram, 2023)
Knowing the problems related to planning and preparation for spiritual attitudes at SDN Tembong 2, researchers carried out observations and interviews at the school. By using qualitative research methods in the realm of case study research and literature study. Researchers carried out observations regarding the habituation of spiritual attitudes in schools. The research results show that spiritual attitude preparation or planning is carried out well to achieve school goals. The implementation of spiritual attitudes at SDN Tembong 2 can be carried out optimally if the implementation is carried out by the teachers themselves, especially religious teachers, as well as class teachers, and it is the responsibility of all teachers. The preparations carried out by the teacher in a spiritual attitude are held every month with a meeting with the strategies that must be carried out so that the child gets used to it, guided by the teacher who can be an example for the students.